New approach and strategy in the assessment of labour pain - Czech version of the labour coping pain assessment tool - Puhlová, Eva; Moravcová, Markéta (Neuro endocrinology letters, 2024)
OBJECTIVES: To create a Czech version of the Labor Coping Scale (LCS) evaluation tool intended for midwives when caring for a woman with labor pain, to evaluate its psychometric properties and to find out the opinion on it in clinical practice. MATERIALS AND METHODS: Are use a combination of methods. By using repeated back translation, the Czech version of the LCS tool was created. It included an assessment of the tool's content validity index and a questionnaire survey determining the midwives' approach to labor pain (N = 419), supplemented by a focus group method (N = 16 midwives). RESULTS: A new evaluation tool for the management of labor pain was created - the Pain Coping Scale, which assesses the management of labor pain, not intensity, like previous evaluation scales. It is a tool that maps 5 areas on a scale of 0-10. CONCLUSION: As part of her work, a midwife should be able to adequately assess a woman's management of labor pain, using a suitable tool, to reveal the factors that influence the development and experience of labor pain, and then choose an appropriate strategy in the care of a woman with labor pain. A new LCS labor pain assessment tool could help with this in the Czech environment.
Keywords: Surveys and Questionnaires; Adaptation, Psychological; Pain Measurement; Pregnancy; Humans; Midwifery; Female; dospělí; babictví; lidé; průzkumy a dotazníky; Adult; Labor Pain; ženské pohlaví; adaptace psychologická; Psychometrics; těhotenství; Czech Republic; porodní bolesti; Česká republika; psychometrie; měření bolesti